The Alsea Noun Phrase - Buckley, Eugene (Kansas Working Papers in Linguistics, 1989)
This paper examines the structure of the noun phrase in Alsea, an extinct language of the Oregon Coast., with particular attention to the behavior of a clitic occurring in the second position within the noun phrase.